Mengapa Wajib Pajak Patuh? Peta Global Riset Kepatuhan Pajak Berbasis Sistem, Perilaku, dan Tata Kelola - I Made Abi Wirawan; Lusy (JURNAL ILMIAH EDUNOMIKA, 2026)
Tax compliance is central to fiscal sustainability and state legitimacy, yet prior studies remain fragmented across economic, behavioral, and governance perspectives. This study maps the development, knowledge structure, and evolution of tax compliance research using a bibliometric approach. Data were collected from Scopus-indexed publications (2000–2024) and analyzed with R Studio (bibliometrix package). The findings show that the literature is still dominated by themes of tax systems and enforcement-based compliance, while recent research increasingly addresses tax reform, governance approaches, financial systems, and developing-country contexts. Theoretically, the results indicate that Deterrence Theory alone is insufficient to explain compliance behavior. More integrative frameworks are needed, including the Slippery Slope Framework, which combines authority power and taxpayer trust, and the Theory of Reasoned Goal Pursuit, which frames compliance as conscious, goal-directed behavior. A governance perspective further emphasizes accountability, transparency, and state responsiveness in building trust. This study contributes by integrating fragmented streams of tax compliance research and outlining future agendas focused on digitalization, sustainability, and modern fiscal governance.